The inflammatory bowel disease disk application: A platform to assess patients' priorities and expectations from treatment. Issue 10 (21st September 2021) - Naftali, Timna; Richter, Vered; Mari, Amir; Khoury, Tawifik; Shirin, Haim; Broide, Efrat
Abstract : Objective: Inflammatory bowel disease (IBD) significantly impacts on patients' well‐being. Patients' preferences for treatment outcomes do not necessarily fit physicians' goals. We aimed to investigate patients' priorities and expectations from treatment. Methods: A questionnaire based on the IBD Disk application was distributed to patients through social media. Patient's preferences were assessed by grading the 10 IBD Disk items on a Likert‐type scale from 1 to 10. A cluster analysis was used to classify patients into homogeneous subgroups according to their preferred items, using the K‐means method. Results: Among the 224 patients, 69.2% had Crohn's disease (CD). Their mean age was (38.9 ± 14.9) years and 62.9% were female. More CD patients compared with those with ulcerative colitis were treated with biologics compared with those with ulcerative colitis (71.0% vs 39.1%, P < 0.001). Most IBD Disk items ranked high in patients' preferences for treatment outcomes. Their leading preference was reducing abdominal pain, which was more prominent in CD patients, followed by regulating defecation and energy. Least important were interpersonal interactions, sexual functions, and body image. Patients were categorized into three clusters. Cluster 3 patients gave lower scores to most items and were characterized by tertiary education ( P = 0.001), higher income ( P < 0.001), less active disease ( P = 0.02), and higher prevalence of successful treatment ( P = 0.04). Conclusions: Patients' preferences for treatment outcomes are influenced by higher education, higher income, rural‐dwelling, and disease activity. Better understanding of individual patient's preferences and the factors that affect them might bridge the gap between patients' and physicians' priorities to achieve better teamwork in controlling disease outcomes. Abstract : Leading preferences of patients' with inflammatory bowel disease and their expectations from treatment were reducing their abdominal pain, which was more prominent in patients with Crohn's disease than UC, followed by regulating defecation and increasing their energy level. The least important preferences were improvements in their interpersonal interactions, sexual functions and body image. Patients' preferences are influenced by their education and income levels, whether they reside in rural areas, and the activity of their disease.